The effect of parent-child interaction a prosumer approach to parent education on the cognitive skills and concepts of selected preschool children - Basco, Ellen Grace Simon (1993)
The study reported here describes the development and implementation of a program used to train parents to help their preschool children learn selected cognitive skills and concepts. Patterned after the Parent-Child Interaction (PCI) Program developed by Marilyn Coleman and Lawrence Ganong, the program has a prosumer approach in that parents were not passive consumers of information but were active participants in their learning. Forty volunteer parents, twenty from a middle-income community and twenty from a depressed area, together with their children aged 2 1/2 to 4 years of age were involved in the study. Half of the parents and children from each community were exposed to the program to comprise the experimental groups. The other half became the control groups. The parents in the experimental groups met in groups to learn ways of interacting with their children using toys in learning episodes done at home. A cognitive concepts and skills test was developed to measure children's knowledge of selected skills and was administered prior to the six-week program and every week after every learning episode. Another instrument was developed to gauge parents' knowledge in helping their children learn effectively. It was administered prior to and a week following the end of the six-week program. Children belonging to the experimental groups showed significant gains in cognitive concepts and skills namely: auditory, perception, color discrimination and seriation, over the control group. The null hypothesis stating equal gains in cognitive concepts and skills of the experimental and control group children was rejected and the alternative hypothesis of significant higher gains was accepted. The null hypothesis stating the absence of factors that give significant information on gain was rejected and the alternative hypothesis of having at least one factor giving significant information on gain is accepted. The one factor that explained gain was the treatment given (experimental or control). The factors socio-economic status, age of parent, and sex of children were seen to affect gain only in relation to treatment given. Among the children given the experimental treatment, those who came from the depressed community, had older parents, were males had greater mean gains and thus seemed to have benefited more from the program than children from the middle class families. Parents likewise showed significant higher post test than pretest scores in knowledge on how children learn, how to teach children effectively, and their roles in the teaching-learning process. The null hypothesis stating equal pretest and post test scores of parents is rejected and the alternative hypothesis of significantly higher post test scores is accepted. The null hypothesis stating the absence of factors that give significant information on parents' gain scores on the instrument that gauged their knowledge in how to teach their children, was rejected. The alternative hypothesis of having at least one factor giving significant information on parents' gain scores is accepted. The variables - educational attainment of parent and socio-economic status were seen to affect gain. Parents who belonged to the depressed community and who were less educated had greater mean gains and therefore seemed to benefit more from the intervention given.